AUGUSTINE, SCRIPTURA, AND CITY OF GOD - Torseth, Robb Lawrence (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
This article discusses how Augustine describes the City of God in his understanding of the Bible. The results of the article Augustine's use of Scripture in the City of God is authoritative and paradigmatic, providing the only sufficient foundation of truth for the development of his civic theology. This is apparent in the way he introduces Scriptural passages as either the final word in a matter or by interweaving his sentences and paragraphs therewith in both a theological and illustrative fashion. In doing so, he creates a sort of 'matrix' or blanket of Scripture to support, define, and perpetuate his arguments from beginning to end. This would not be possible if he did not believe the Bible to have been the sole source of divine grace and truth, a sufficient and inerrant testimony from God to man and the ultimate source of authority for faith.